Is virtual reality emotionally arousing? Investigating five emotion inducing virtual park scenarios. Issue 82 (October 2015) - Felnhofer, Anna; Kothgassner, Oswald D.; Schmidt, Mareike; Heinzle, Anna-Katharina; Beutl, Leon; Hlavacs, Helmut; Kryspin-Exner, Ilse
Abstract: Following the idea of using virtual environments (VEs) as mood induction procedures (MIPs), this study set out to examine whether five different virtual park scenarios would each elicit a specific affective state (i.e., joy, sadness, boredom, anger and anxiety). Within this main objective, a subset of two additional goals was identified: first, to analyze whether the sense of presence would differ across emotionally charged VEs, and second, to examine the link between a more objective measure of affective arousal, electrodermal activity (EDA), and presence. Following a between-subject design, 120 students were randomly assigned to one of the five VEs. Results show that almost all of the five virtual park scenarios were able to elicit the intended emotion. Additionally, presence levels were the same across all VEs suggesting that presence did not confound the emotional reaction to the VEs. Furthermore, EDA seems to be a poor indicator of presence as it is not significantly correlated with self-reported presence. The implications of these findings for both future research and practice are addressed in a comprehensive discussion. Highlights: Four virtual park scenarios elicited the intended emotional states. Presence levels were the same across different virtual environments. Skin conductance level seems to be a poor indicator of presence.